Intermittent hypoxic exposure with high dose of Arginine impact on circulating mediators of tissue regeneration - Zembron-Lacny, A.; Gramacki, A.; Wawrzyniak-Gramacka, E.; Tylutka, A.; Hertmanowska, N.; Kasperska, A.; Czuba, M. (Nutrients, 2020)
Intermittent exposure to hypoxia (IHE) increases production of reactive oxygen and nitrogen species which, as signalling molecules, participate in tissue injury-repair-regeneration cascade. The process is also stimulated by arginine whose bioavailability is a limiting factor for NO synthesis. The effects of IHE in combination with arginine (Arg) intake on myogenesis and angiogenesis mediators were examined in a randomized and placebo-controlled trial. Blood samples were collected from 38 elite athletes on the 1st, 7th and 14th days during the training camp. The oral doses of arginine (2 × 6 g/day) and/or IHE using hypoxicator GO2Altitude (IHE and Arg/IHE) were applied. Serum NO and H2O2 concentrations increased significantly and were related to muscle damage (CK activity >900 IU/mL) in IHE and Arg/IHE compared to placebo. The changes in NO and H2O2 elevated the levels of circulating growth factors such as HGF, IHG-1, PDGFBB, BDNF, VEGF and EPO. Modification of the lipid profile, especially reduced non-HDL, was an additional beneficial effect of hypoxic exposure with arginine intake. Intermittent hypoxic exposure combined with high-dose arginine intake was demonstrated to affect circulating mediators of injury-repair-regeneration. Therefore, a combination of IHE and arginine seems to be a potential therapeutic and non-pharmacological method to modulate the myogenesis and angiogenesis in elite athletes